The man that got away - Truss, Lynne (Truss, Lynne. Constable Twitten mystery., 2019)
1957: In the beach town of Brighton, music is playing and guests are sunning themselves, when a young man is found dead, dripping blood, in a deck chair. Constable Twitten of the Brighton Police Force has a hunch that the fiendish murder may be connected to a notorious nightspot, but his captain and his colleagues are-as ever-busy with other more important issues. Inspector Steine is being conned into paying for the honor of being featured at the Museum of Wax, and Sergeant Brunswick is trying (and failing) to get the attention of the distraught Brighton Belles who found the body. As the case twists and turns, Constable Twitten must find the murderer and convince his colleagues that there's an evil mastermind behind Brighton's climbing crime rate.